Twenty years of histochemistry in the third millennium, browsing the scientific literature - Pellicciari, Carlo (European journal of histochemistry, 2020)
Over the last twenty years, about 240,000 articles where histochemical techniques were used have been published in indexed journals, and their yearly number has progressively increased. The histochemical approach was selected by researchers with very different scientific interests, as the journals in which these articles were published fall within 140 subject categories. The relative proportion of articles in some of these journal categories did change over the years, and browsing the table of contents of the European Journal of Histochemistry, as an example of a strictly histochemical journal, it appeared that in recent years histochemical techniques were preferentially used to mechanistically investigate natural or experimentally induced dynamic processes, with reduced attention to purely descriptive works. It may be foreseen that, in the future, histochemistry will be increasingly focused on studying the molecular pathways responsible for cell differentiation, the maintenance or loss of the differentiated state, and tissue regeneration.